The CAMP study: feasibility and clinical correlates of standardized assessments of substance use in a youth psychiatric inpatient sample - Jillian Halladay; Laurie Horricks; Michael Amlung; James MacKillop; Catharine Munn; Zil Nasir; Rachel Woock; Katholiki Georgiades (BMC, 2021)
Abstract Background To determine: (a) the feasibility and acceptability of administering a standardized electronic assessment of substance use and other mental health concerns to youth admitted to an inpatient psychiatric unit, and (b) the prevalence and clinical correlates of substance use in this sample. Methods The sample included 100 youth between the ages of 13 to 17 years admitted to an inpatient psychiatric unit in Ontario, Canada between September and November 2019 (78% response rate). Youth data were comprised of electronic self-reported assessments (during hospitalization and 6-months following) and chart reviews (99% consented; historical and prospective). Frontline staff completed a self-report survey assessing their perceptions of the need for standardized substance use assessments, training, and interventions on the unit (n = 38 Registered Nurses and Child and Youth Workers; 86% response rate). Analyses included descriptive statistics, correlations, regression, and qualitative content analysis. Results Feasibility of standardized youth self-reported mental health and substance use assessments was evident by high response rates, little missing data, and variability in responses. 79% of youth had used at least one substance in their lifetime; 69% reported use in the last 3 months. Substance use was positively correlated with severity of psychiatric symptoms (τb 0.17 to 0.45) and number of psychiatric diagnoses (τb 0.17 to 0.54) at index. Based on prospective and retrospective data, substance use was also positively related to mental health symptom severity at follow-up and repeat mental health related hospital visits. Frontline staff reported a need for standardized assessment, training, and interventions on the unit, indicative of acceptability. Conclusions This study demonstrated the feasibility, acceptability and clinical importance of administering a standardized mental health and substance use assessment among youth experiencing psychiatric hospitalization.